Identification of Immunogenic Proteins in Early and Advanced Stages of Breast Cancer: An Immunoproteomics Study - Zeinab Mohammadi; Mahdi Pouramir; Mohammad Reza Haghshenas; Sedigheh Tahmasebi; Abbas Ghaderi (Middle East Journal of Cancer, 2023)
Background: Early detection of breast cancer (BC) is extremely important as late diagnosis has been associated with a high rate of mortality. Immunogenic proteins and autoantibodies have been considered as favorable targets for early detection and targeted therapy in cancer. Accordingly, the present study aimed to identify the immunogenic antigens in both early and advanced stages of BC via a serologic proteome analysis (SERPA) approach.Method: This is a case-control study wherein we separated the proteins from BC tissues in the early stages (n = 10) and advanced stages (n = 10) utilizing two-dimensional electrophoresis (2DE) and then transferred them onto a Polyvinylidene Difluoride (PVDF) membrane. To explore the tumor antigens reacting with antibodies, two-dimensional (2D) blots of tumor tissues in the early and advanced stages were separately probed with the sera from the same patients. Afterwards, we identified antibody-reactive proteins via liquid chromatography with tandem mass spectrometry (LC-MS/MS).Results: Fibrinogen beta chain (FGB), protein deglycase DJ-1(PARK7), and peroxiredoxin-2 (PRDX2) were the highly reactive antigens identified in the earlystage patients. In addition, RuvB-like1 (RUVBL1) and triose phosphate isomerase (TPI) were recognized as the immune reactive proteins in the late-stage patients.Conclusion: The results herein revealed that the immune-proteome pattern of BC patients changes along with tumor progression from primary to advanced stages. Moreover, immunogenic proteins seemed to stimulate the humoral immune system to produce autoantibodies in the initiation phase of BC; these autoantibodies could be employed as complementary factors for early detection of BC. The findings are however preliminary, and further studies with a larger sample size are required for verification and validation of previous findings.